Ionic currents in ventricular myocytes isolated from the heart of a patient with idiopathic cardiomyopathy - Nánási Péter Pál; Varró András; Lathrop D A (1992)
Whole-cell configuration of the patch-clamp technique was applied to record ionic currents from human ventricular myocytes isolated from a cardiac transplant patient with idiopathic cardiomyopathy. Inward calcium current, transient outward current, and inward rectifier potassium current were recorded, while no discernible delayed rectifier potassium current was observed. Thus the currents that underlie electrical activity in human ventricular myocytes appear to resemble those reported earlier in canine and rabbit ventricular myocytes.
Keywords: Klinikai orvostan